The problem of education in Indonesia is the independent curriculum the solution - Fika Damayanti; Hendis Vivien; Marline Situmorang; Teguh Trianung; Supadi (Institute of Computer Science (IOCS), 2023)
Indonesian education requires appropriate quality improvement to meet the challenges and needs of its time and the curriculum is considered the most important part of the educational process. This study aims to find out whether the Ministry of Education and Culture policy regarding the independent curriculum is appropriate as an answer to the condition of education problems in Indonesia. This research used descriptive qualitative literature with a literature review method. This study uses 22 articles as data sources. The results of this study concluded that the independent curriculum was successful in tackling learning during the pandemic, providing hope in restoring education in Indonesia, giving teachers the widest possible space to develop their own potential and being able to improve the quality or quality of education in Indonesia in the 21st century. So that the Ministry of Education and Culture policy regarding changing the curriculum is considered appropriate.